North-South Dimension in Corporate Responses to Climate Challenges: Legal Insights - Konasinghe, K.L.; Dawood, S. (University of Colombo, 2024)
The power dynamics between the global North and South play a critical role in determining collective action towards addressing climate change and environmental degradation. The overutilization of resources by the North as a group of nations, since the Industrial Revolution, possesses relatively a bigger share of the historical guilt over the unequal distribution of common global property. Until recently, International Environmental law primarily focused on adaptation and mitigation within interstate frameworks. However, the growing emphasis on loss and damage claims, particularly from the Global South, has brought attention to the potential extension of legal parameters that include various non-state parties. This is supported by the evolution of international law ...
Keywords: Climate Change; Corporate Governance; Loss and Damage; CBDR; CSR